Comparative pharmacokinetic and pharmacodynamic evaluation of branded and generic formulations of meloxicam in healthy male volunteers - Tacca, Mario Del (Dove Medical Press, 2013)
PURPOSE: The primary aim of the present study was to assess the pharmacokinetic bioequivalence between a generic formulation of meloxicam 15 mg tablets (Meloxicam Hexal) and its respective brand product (Mobic), in order to verify whether the generic product conforms to the regulatory standards of bioequivalence in the postmarketing setting. As a secondary exploratory aim, the pharmacodynamic effects of the two formulations were also evaluated by means of rating scales following hyperalgesia induced by cutaneous freeze injury. SUBJECTS AND METHODS: A single 15 mg dose of generic or branded meloxicam tablets was administered to 24 healthy male volunteers in a crossover fashion. Plasma samples, collected for 24 hours after dosing, were assayed for meloxicam concentration by a validated highperformance liquid chromatography method. RESULTS: The analysis of pharmacokinetic parameters did not show any significant difference between the two meloxicam formulations: the 90% confidence intervals fell within the acceptance range of 80%–125% (0.84–1.16 for area under the curve [0–24], and 0.89–1.23 for peak concentration). No difference in the pharmacodynamic end point was observed between the two groups. CONCLUSION: The pharmacokinetic profiles of the two meloxicam formulations confirm the regulatory criteria for bioequivalence; pharmacodynamic data indicate a similar antihyperalgesic effect. The two formulations can be used interchangeably in the clinical setting.